Marketing Strategies in Apple Industry - An Empirical Study in Himachal Pradesh and Jammu & kashmir - Rauf, Abdul; Saraf, Sajad A. (Indian Journal of Marketing, 2011)
Apple (Malus pumila) is commercially the most important temperate fruit and is fourth among the most widely produced fruits in the world after banana, orange and grape. Apple is widely grown in the temperate regions of the world, and in the year 2007-08, the world apple production was estimated at 6.35 crore tonnes. China ranks first in the matter of apple production, accounting for nearly 36 per cent of global production followed by United states - 6.65 per cent, Turkey - 4.25 per cent, Poland - 4.13 per cent, Iran - 4.01 per cent, France - 3.64 per cent and, Italy - 3.31 per cent. The average share of Indian apple production based on 2007-08 data was 2.50 per cent and ranked 10th among the apple producing countries of the world. At present, India has achieved a production potential of 17.39 lakh tonnes annually. During the period 1973-74 to 2007-08, apple production in India recorded a growth of 2.42 per cent per annum. Presently, apple occupies 4.8 per cent of area under total fruits and contributes to 3.5 per cent towards total fruit production in India. In India, the production of apple is mainly confined to Jammu and Kashmir, Himachal Pradesh, Uttarakhand, Arunachal Pradesh, Nagaland and Sikkim. However, Himachal Pradesh and Jammu and Kashmir are the most important states, together accounting for 81 per cent of the total area and 92.63 per cent of the production in the country. In Himachal Pradesh, almost 92000 hectares of land is under apple production. 80 per cent of the people in the state are directly or indirectly associated with this business. The apple in Himachal Pradesh alone accounts for more than 46.50 percent of area and 73.77 percent of production of all fruits grown in the state. In Jammu & Kashmir, the area under fruit cultivation has increased significantly - from 45,900 hectare to 1,11,814 hectares during period 2007-08. Apple occupied 44.10 percent of area and 90 percent of production of total fruits in the state. Kashmir is major apple-producing region of the country. It is the mainstay of the local economy with lakhs of rural people eking out their livelihood from this industry.